RUANG INTERAKTIF KAMPUNG BEKELIR TANGERANG - Careen Leo; Doddy Yuono (Jurusan Arsitektur dan Perencanaan, 2022)
Kampung Bekelir, which was originally a tourism village, succeeded in attracting newcomers with several interesting and educational attractions. The village is very focused on the tourism aspect and in the end ignores the needs of its residents. The imbalance between communal space and tourism sites in Kampung Bekelir has resulted in the programs losing their value and attractiveness. It is caused by many activities that have not been accommodated and the lack of space for the community. This issue is quite crucial because Kampung Bekelir, which is initially a tourism village, slowly being degraded and losing its function and identity. Therefore, it is necessary to apply urban acupuncture which aims to touch the collective soul of the city. The collective soul is reflected through the collective consciousness of the community which can eventually become a reality. By using the guidelines in the 11th points of Sustainable Development Goals, environtmental-focused design is carried out using the in-fill method and the application of typology with programs that focus on aspects of education, economy, people's welfare to achieve an area with sustainable settlements. Keywords: Degradation in an environtment; Urban Acupuncture; In fill methods Abstrak Kampung Bekelir yang pada awalnya merupakan kampung pariwisata berhasil memikat pendatang baru dengan beberapa atraksi yang menarik dan edukatif. Kampung tersebut sangat berfokus pada aspek pariwisatanya dan pada akhirnya mengabaikan kebutuhan warganya. Ketidakseimbangan antara ruang komunal dan situs pariwisata di Kampung Bekelir Tangerang karena banyaknya kegiatan belum terakomodasi dan kurangnya ruang untuk komunitas mengakibatkan objek pariwisata di kawasan Kampung Bekelir kehilangan nilai dan daya tarik. Isu ini menjadi cukup krusial karena kampung Bekelir yang merupakan kampung pariwisata perlahan-lahan mengalami degradasi dan kehilangan fungsi serta identitasnya sebagai sebuah kampung wisata. Maka itu diperlukannya penerapan akupunktur perkotaan yang bertujuan untuk menyentuh jiwa kolektif kota. Jiwa kolektif direfleksikan melalui kesadaran kolektif dari masyarakat yang pada akhirnya dapat menjadi kenyataan. Dengan menggunakan panduan dalam tujuan ke-11 dari pembangunan berkelanjutan (Sustainable Development Goals), perancangan kawasan dilakukan dengan metode in fill dan penerapan tipologi dengan program yang berfokus pada aspek edukasi, ekonomi, kesejahteraan warga untuk mencapai sebuah kawasan dengan pemukiman berkelanjutan.